THE EVIDENCE SYSTEM FOR SEXUAL VIOLENCE CASES INVOLVING PERSONS WITH DISABILITIES AS VICTIMS - Sofiatun Sofiatun; Indah Sri Utari; Rini Fidiyani (Awang Long Law Review, 2026)
Sexual violence against persons with disabilities is a crime that requires full attention. Persons with disabilities, as victims of crime, must receive justice. This study aims to identify the obstacles experienced by persons with disabilities in the evidentiary process of law enforcement and to provide information about a disability-friendly evidentiary system. This research is normative in nature, with data sources derived from secondary data. The data were collected, classified, and processed according to the discussion to provide answers to the issues raised, then presented descriptively. The results show that obstacles may arise from persons with disabilities themselves, law enforcement officers, and the still-developing understanding of sexual violence. Regarding the evidentiary system, there is a need to update regulations to facilitate the evidentiary process. The evidentiary system based on Law No. 12 of 2022 offers a disability-friendly approach to achieving justice. In implementing the evidentiary process, disability-friendly measures must also be considered, as stipulated in Government Regulation No. 39 of 2020 concerning Reasonable Accommodation for Persons with Disabilities in Judicial Processes.